Importance of P-Wave Indices in a Sample of Iraqi Type 2 Diabetic Patients - Al-Auqbi, Tawfeeq F R; Funjan, Mawada Mousa; Al-Karawi, Isam N S (Al-Nahrain Journal of Science, 2012)
Background: Diabetes mellitus has a negative impact on the cardiovascular system; P-wave indices were considered to reflect the discontinuous and inhomogeneous propagation of sinus impulses and prolongation of atrial conduction time.Objectives: to know importance of P-wave indices and significant of its use for prediction and evaluation of diabetic complication in type 2 diabetics.Methods and Results: A case control study, Dec. 2011, on diabetics (n=88) and healthy relatives (n= 70) were conducted in the NDC. Comparing both groups for age, sex, resting heart rate and BMI revealed insignificant differences, P > 0.05. P-wave indices of diabetics shown absence of any correlation with the age, duration of diabetes, FPG, BMI, resting heart rate and HDL; But, it shown weak correlation with HbA1c, Serum cholesterol, serum triglycerides and LDL. P-wave indices show significant higher values in diabetics than in healthy subjects, P < 0.05, except for the Pmin, P > 0.05.Conclusions: P-wave indices (Pmean, Pmax, and Pd) were significantly higher in diabetics than the healthy individuals. P-wave indices of diabetics have no effect on gender, age and BMI; but, have weak correlation with HbA1c, Serum cholesterol, serum triglycerides and LDL.